Applying value-belief-norm theory to investigate students’ waste prevention behaviour - Smilingytė, Ernesta; Šorytė, Dovilė (Psichologija, 2021)
Even though the increasing amount of waste is one of the biggest environmental challenges we currently face, surprisingly little is known about the psychological factors of waste prevention behaviour. The purpose of the study is to examine whether students‘ waste prevention behaviour can be predicted by the Value-Belief-Norm theory. In this paper, we report results from a questionnaire study of 221 students aged from 18 to 26 years. It was found that the Value-Belief-Norm theory could indeed explain students‘ waste prevention behaviour. As expected, findings indicate that high endorsement of biospheric values is associated with a strong ecological worldview, which was related to an increased awareness of environmental consequences. Those beliefs led to stronger personal norms, which were associated with more frequent waste prevention behaviour. Understanding students‘ waste prevention behaviour and the factors predicting it is a key step that could help to reduce the amount of waste that is generated. It is particularly relevant among students because higher education environment could be an effective place to increase students‘ pro-environmental behaviour and connect this behaviour with their values, beliefs and norms.